"Colleague postgraduate supervision" and the production of space in higher education: a duoethnographic analysis. (18th September 2020) - Madikizela-Madiya, Nomanesi; Atwebembeire, John Mushomi
Abstract : Purpose: In this paper we contribute knowledge to the postgraduate supervision discourses by reflecting on our socio-spatial experiences of being supervised by colleagues, a process that we refer to as colleague postgraduate supervision (CPS). Design/methodology/approach: We followed a duoethnographic research design by dialogically presenting and exploring our lived experiences of CPS and critiquing and questioning the meanings we give to those experiences. The experiences shared arose from two different contexts: a contact university and an open distance learning university. Findings: The reflection suggests that social values of trust, compassion and care in CPS can outrun the spatial constraints for the benefit of the supervisees in the relationship. However, the colleagues in the CPS can also experience some subtle power dynamics and tensions that produce a constraining space, if the CPS process is not well communicated. Originality/value: While CPS is a common practice in some universities, there is limited research that pays attention to its socio-spatiality, that is, the interaction between the social and the spatial aspects of this practice.